Effects of Labor Efficiency in Human Resource Management - Ergashev R.H; Mirjahon Alikulov (International Journal on Economics, Finance and Sustainable Development, 2022)
The article provides suggestions and recommendations on ensuring the sustainable development of industrial enterprises in the context of innovative development of the economy, reducing labor costs for production, the impact of improving the quality and efficiency of labor on human resources.